Graft-versus-host disease after anti-CD19 chimeric antigen receptor T-cell therapy following allogeneic hematopoietic cell transplantation: a transplant complications and paediatric diseases working parties joint EBMT study - Ortí, Guillermo; Peczynski, Christophe; Boreland, William; O’Reilly, Maeve; von Bonin, Malte; Balduzzi, Adriana; Besley, Caroline; Kalwak, Krzysztof; Ryhänen, Samppa; Güngör, Tayfun; Wynn, Robert F.; Bader, Peter; et al. (Leukemia, 2025)
In patients diagnosed with B-acute lymphoblastic leukemia (B-ALL) or B-non-Hodgkin’s lymphoma (B-NHL) relapsing after allogeneic stem cell transplantation (allo-HCT), it is a standard practice to perform anti-CD19 chimeric antigen receptor (CAR) T-cell therapy. When collected from the patient after allo-HCT, the produced CAR-T cells are likely to be donor T-cell-derived, creating unknown safety risks due to their potential allo-reactivity. We therefore performed an EBMT registry-based study on the incidence of graft-versus-host disease (GvHD) in this setting. We included 257 allo-HCT patients (n = 172 ≥ 18 years) with B-ALL or B-NHL, treated with anti-CD19 CAR T-cells (tisagenlecleucel n = 184, brexucabtagene autoleucel n = 43 and axicabtagene ciloleucel n = 30), between 2018 and 2022. Three patients developed aGvHD, whereas 6 patients developed cGvHD after CAR T-cell. The 100-day cumulative incidence (CI) of new aGvHD was 1.6% and the 12-month CI of new cGvHD was 2.8%. The 1-year GvHD relapse-free survival and non-relapse mortality were 52.1% and 4.7%, respectively. Last, with a median follow up of 18.8 months, the 1-year overall survival was 76.8%. In summary, the GvHD rate in allo-HCT patients treated with CAR T-cell therapy is relatively low. Our data support the view that GvHD is not a major safety issue in this setting.